CONCEPTUAL APPROACHES TO THE RAPID DETECTION OF CAMPYLOBACTER SPP. IN MEAT OF SLAUGHTER ANIMALS - D. S. Bataeva; M. Yu. Minaev; Yu. K. Yushina; O. V. Sokolova; E. V. Zajko (Теория и практика переработки мяса)
The modern approach to quality assurance of food products based on the ISO 9000 standards indicates the need for the implementation of quality management systems in processing plants. According to the analysis of scientific publication databases (Science Direct and Web of Science), it is established that only 0.5–1.7% of publications are related to studying meat of slaughter animals (except for birds) concerning the presence of Campylobacter. The priority method of investigation is PCR. Ready-to-use PCR test system was developed for the detection of Campylobacter spp. on the basis of selected gene-specific primers to bacteria of Campylobacter genus. Specificity of the test system is established for Gram-negative bacteria of Salmonella, Escherichia, and Proteus genera, and for oxidase-positive Aeromonas. Gene-specific primers for Campylobacter were selected and ready-to-use PCR test system was developed on their basis. It was found that the selected primers have 100% convergence to the genome of Campylobacter genus bacteria, the PCR efficiency is not less than 95%, and the detection limit is not more than 1× 104 CFU/g. When estimating the specificity of the primers, it was taken into account that the bacteria of Campylobacter genus may be incorporated in a consortium with intestine microbiome, mainly with Enterobacteriaceae and lactic acid bacteria. However, Bolton’s enrichment medium is selective and, during the cultivation process, suppresses the growth of Gram-positive lactic acid bacteria. It was found that the selected primers were 100% specific and did not give false positive reactions with this group of microorganisms. The developed test system was successfully validated in a cycle of qualitative tests in the FEPAS system and implemented into laboratory practice. It was proved that the developed test system may be used both in screening at the stages of Campylobacter enrichment and in identification of pure culture of the microorganism.